The Economic Implications of Public Disability Insurance in the United States - Danzon, Patricia M. (Journal of Labor Economics, 1993)
A review of previous analyses of labor supply effects of Social Security Disability Insurance (DI) concludes that estimates of labor supply effects and net social costs are upward biased because they ignore interactions between DI and other insurances. A model of optimal insurance, postinjury accommodations, and labor supply shows that reduction in labor supply and increase in consumption when disabled do not necessarily imply moral hazard. Optimal postinjury accommodations vary inversely with firm size. The Americans with Disabilities Act will reduce wages and labor supply of healthy workers, particularly in small firms. Effects on labor supply of the disabled are ambiguous.